International Judicial Legitimacy New Voices and Approaches - Chaib, André Nunes (Studies of the Max Planck Institute Luxembourg for International, European and Regulatory Procedural Law, 2020)
Zusammenfassung Armin von Bogdandy und Ingo Venzke stellten mit "In Whose Name?" bereits 2014 die grundsätzliche Frage nach der Legitimität internationaler Gerichtshöfe. Der vorliegende Band führt die Debatte weiter: Woraus schöpfen internationale Organisationen und Gerichte ihre Legitimität und wie tragen sie zur Demokratisierung des Völkerrechts bei? Wie steht es um die demokratische Legitimität internationaler Menschenrechtsgerichtshöfe? Der Band bietet eine breite Diskussion zu aktuellen Fragen des internationalen Rechts. Abstract These texts on the legitimacy of international courts were framed as a direct reaction to arguments put forward in the book "In Whose Name?" by Armin von Bogdandy und Ingo Venzke. The subjects ranged from a comparison between international organizations and international courts and how they can contribute to democratize international law to assessing the democratic legitimacy of international human rights courts. Therefore the collection is dealing with both theoretical and practical questions regarding the legitimacy of international courts and how such problems relate to fundamental problems of our times.